(untitled) (Eurasian Journal of Ecology, 2022)
The article takes an actual topic for the present and carried out work to determine the intensity of erosion processes using the Smith method of the Olenty River basin of the West Kazakhstan region. The purpose of this work was to determine the process of soil erosion in the Olenty River basin for various types of land use. To determine soil flushing, the following were used: erosion potential of sediments, soil type, mechanical composition, slope steepness, vegetation, types of plowing, erosion forecast model, universal soil loss equation and the ArcGIS 10.4 program. The southern part of the river basin has a soil flushing rate from 0 to 0.06 t/ha per year. These lands are mainly used for pastures and small areas of territory for haymaking, located in most cases on chestnut soils and small salt marshes, the mechanical composition is mainly dominated by heavy loam. This territory occupies about 40% of the entire river basin. The central and northern parts have different indicators and range from the lowest to the highest. The highest rate of soil flushing is 1.57 – 5.96 t/ha per year are arable lands located mainly on chestnut soils, having a mechanical composition dominated by medium and heavy loam, and arable lands with the highest rate are characterized by a territory with high rainfall and a steeper slope. These indicators of soil flushing from 0.45 to 1.57 t/ha per year also belong to arable land, but unlike the previous class, these arable lands are located in most cases on soils that are mechanically related to medium loam. According to the results of the study, the highest rate of soil flushing falls on arable land, the average is about 1.50 t/ha per year, which corresponds to the “acceptable level of loss”. Key words: erosion processes, river basin, WKO, GIS, soil.